Sibling Similarity in Education Across and Within Societies - Grätz Michael; Barclay Kieron J; Wiborg Øyvind N; Lyngstad Torkild H; Karhula Aleksi; Erola Jani; Präg Patrick; Laidley Thomas; Conley Dalton (Duke University Press, 2022)
The extent to which siblings resemble each other measures the omnibus impact of family background on life chances. We study sibling similarity in cognitive skills, school grades, and educational attainment in Finland, Germany, Norway, Sweden, the United Kingdom, and the United States. We also compare sibling similarity by parental education and occupation within these societies. The comparison of sibling correlations across and within societies allows us to characterize the omnibus impact of family background on education across social landscapes. Across countries, we find larger population-level differences in sibling similarity in educational attainment than in cognitive skills and school grades. In general, sibling similarity in education varies less across countries than sibling similarity in earnings. Compared with Scandinavian countries, the United States shows more sibling similarity in cognitive skills and educational attainment but less sibling similarity in school grades. We find that socioeconomic differences in sibling similarity vary across parental resources, countries, and measures of educational success. Sweden and the United States show greater sibling similarity in educational attainment in families with a highly educated father, and Finland and Norway show greater sibling similarity in educational attainment in families with a low-educated father. We discuss the implications of our results for theories about the impact of institutions and income inequality on educational inequality and the mechanisms that underlie such inequality.